Angiotensin Receptor–Neprilysin Inhibition: New Therapeutic Concept for the Management of Chronic Heart Failure: Development, Clinical Implications, and Future Perspectives. (July 2017) - Havakuk, Ofer; Elkayam, Uri
The novel combination sacubitril/valsartan represents a new therapeutic approach in the management of heart failure. With the simultaneous blockage of the enzyme neprilysin (by sacubitril) and angiotensin II receptors (by valsartan), this combination reduces the degradation of natriuretic peptides and other counterregulatory peptide systems while avoiding the deleterious effect of angiotensin II receptors activation and thereby encompasses a beneficial impact of 2 important neurohormonal pathways activated in heart failure. As opposed to previously tested neprilysin inhibitors, sacubitril/valsartan represents a more effective method in reducing morbidity and mortality in heart failure, while preserving a safety profile comparable to well-established, standard, angiotensin-converting enzyme inhibitor's therapy.